Exploring the ‘Everyday’ in Colin Wilson’s The Black Room and The Personality Surgeon - Sanjay Kumar; Muzaffar Ahmad (Sanglap: Journal of Literary and Cultural Inquiry)
This paper attempts to explore and analyse the idea of ‘Everyday consciousness’ in Colin Wilson’s two fictional works, The Black Room and The Personality Surgeon from the perspective of the concept of ‘natural attitude’ put forth by Edmund Husserl. As psycho-physical and spatio- temporal beings, we perpetually remain held in the thrall of ‘everyday’. Husserl terms it as the ‘natural attitude – a state of consciousness where we act in naivety and unreflectiveness without paying attention to how consciousness functions while going through different experiences. Wilson typically calls this state as ‘robot’- a state of mechanistic consciousness where we hardly reflect back, but go on dragging through the routine of everyday existence. The ‘robot’ tends to reduce the amount of ‘conscious’ activity, thus making the reality shadowy and existence inauthentic. This phenomenological analysis is crucial in fetching us a recognition and understanding of the ‘everyday’ which has implications for how we ‘normally’ act in the ‘everyday’ and how it can be changed qualitatively.